An Alternative to Online Travel Agencies for Retention of Hotel Customers - Riccardo Bonazzi; Roland Schegg (Proceedings of the ENTRENOVA - ENTerprise REsearch InNOVAtion Conference, Rovinj, Croatia, 8-9 September 2016, 2016)
This paper describes a service that allows hotels to reduce their dependency form online travel agencies, such as Booking.com or Expedia. Online travel agencies are extremely helpful to increase the number of new reservations of most hotels, but they seem to be less effective for niche hotels that seek for recurring customers. By following the guidelines for design research, we seek to develop a new online service, which combines existing solutions to (1) acquire new clients, (2) book a room on the website of the hotel and (3) retain the customer after service delivery. We illustrate a case study of a hotel, which has reduced the number of clients obtained via Booking.com by following our guidelines.
Keywords: L8; Z3; 330; online travel agency; hotel; business model innovation; tourism